2018
DOI: 10.1136/bmj.k3793
|View full text |Cite
|
Sign up to set email alerts
|

Six months versus 12 months dual antiplatelet therapy after drug-eluting stent implantation in ST-elevation myocardial infarction (DAPT-STEMI): randomised, multicentre, non-inferiority trial

Abstract: ObjectiveTo show that limiting dual antiplatelet therapy (DAPT) to six months in patients with event-free ST-elevation myocardial infarction (STEMI) results in a non-inferior clinical outcome versus DAPT for 12 months.DesignProspective, randomised, multicentre, non-inferiority trial.SettingPatients with STEMI treated with primary percutaneous coronary intervention (PCI) and second generation zotarolimus-eluting stent.ParticipantsPatients with STEMI aged 18 to 85 that underwent a primary PCI with the implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 47 publications
2
117
1
2
Order By: Relevance
“…Moreover it has been shown that patients who discontinued DAPT between 1 and 12 months after implantation of the R‐ZES had low rates of ST and adverse cardiac outcomes and recently the DAPT STEMI trial provided an important answer regarding the noninferiority of 6 months of DAPT compared to 12 months DAPT after R‐ZES implantation in the setting of pPCI for STEMI . Indeed 6‐month DAPT was noninferior in a patient‐oriented composite clinical endpoint versus the regimen of 12 months DAPT showing that a shorter DAPT duration is also feasible and safely applicable if clinically required in STEMI patients who received a R‐ZES.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it has been shown that patients who discontinued DAPT between 1 and 12 months after implantation of the R‐ZES had low rates of ST and adverse cardiac outcomes and recently the DAPT STEMI trial provided an important answer regarding the noninferiority of 6 months of DAPT compared to 12 months DAPT after R‐ZES implantation in the setting of pPCI for STEMI . Indeed 6‐month DAPT was noninferior in a patient‐oriented composite clinical endpoint versus the regimen of 12 months DAPT showing that a shorter DAPT duration is also feasible and safely applicable if clinically required in STEMI patients who received a R‐ZES.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efforts in reducing the duration of DAPT have been, so far, prevented by the fear of late (>30 days) and very late (>1 year) stent thrombosis, events that have prevented the spread of DES for many years. e development of newer generations of DES, with thinner struts, more predictable drug release, and lower grade of inflammation, thanks to biodegradable polymer or polymer-free technology, have allowed a faster re-endothelization, therefore reducing the rate of thrombotic complications to neglectable levels (<1%) and offering promising outcomes even with a shorter 1 to 6 months DAPT [12][13][14][15][16]22].…”
Section: Dual Antiplatelet Therapy (Dapt) Duration In Acs: the Standamentioning
confidence: 99%
“…Since 2012, after the publication of the PRODYGY trial [23], that randomized 2013 patients to 6 vs. 12 months of DAPT after PCI, further 14 trials have addressed the feasibility of reducing the period of DAPT [15,16,[24][25][26][27][28][29][30][31][32][33][34][35], documenting the noninferiority of a shorter strategy as compared with the traditional 12 months in terms of antiischemic protection.…”
Section: Dual Antiplatelet Therapy (Dapt) Duration In Acs: the Standamentioning
confidence: 99%
See 2 more Smart Citations